Persistence of Anti-SARS-CoV-2 Antibodies in Long Term Care Residents Over Seven Months After Two COVID-19 Outbreaks - Tanunliong, Guadalein; Liu, Aaron; Vijh, Rohit; Pidduck, Tamara; Kustra, Jesse; Márquez, Ana Citlali; Choi, Alexandra; McLennan, Meghan; Hayden, Althea; Kearney, Christy; Gantt, Soren; Krajden, Mel; et al. (Frontiers in Immunology, 2022)
Background: As part of the public health outbreak investigations, serological surveys were carried out following two COVID-19 outbreaks in April 2020 and October 2020 in one long term care facility (LTCF) in British Columbia, Canada. This study describes the serostatus of the LTCF residents and monitors changes in their humoral response to SARS-CoV-2 and other human coronaviruses (HCoV) over seven months. Methods: A total of 132 serum samples were collected from all 106 consenting residents (aged 54-102) post-first outbreak (N=87) and post-second outbreak (N=45) in one LTCF; 26/106 participants provided their serum following both COVID-19 outbreaks, permitting longitudinal comparisons between surveys. Health-Canada approved commercial serologic tests and a pan-coronavirus multiplexed immunoassay were used to evaluate antibody levels against the spike protein, nucleocapsid, and receptor binding domain (RBD) of SARS-CoV-2, as well as the spike proteins of HCoV-229E, HCoV-HKU1, HCoV-NL63, and HCoV-OC43. Statistical analyses were performed to describe the humoral response to SARS-CoV-2 among residents longitudinally. Findings: Survey findings demonstrated that among the 26 individuals that participated in both surveys, all 10 individuals seropositive after the first outbreak continued to be seropositive following the second outbreak, with no reinfections identified among them. SARS-CoV-2 attack rate in the second outbreak was lower (28.6%) than in the first outbreak (40.2%), though not statistically significant (P>0.05). Gradual waning of anti-nucleocapsid antibodies to SARS-CoV-2 was observed on commercial (median Δ=-3.7, P=0.0098) and multiplexed immunoassay (median Δ=-169579, P=0.014) platforms; however, anti-spike and anti-receptor binding domain (RBD) antibodies did not exhibit a statistically significant decline over 7 months. Elevated antibody levels for beta-HCoVs OC43 (P<0.0001) and HKU1 (P=0.0027) were observed among individuals seropositive for SARS-CoV-2 compared to seronegative individuals. Conclusion: Our study utilized well-validated serological platforms to demonstrate that humoral responses to SARS-CoV-2 persisted for at least 7 months. Elevated OC43 and HKU1 antibodies among SARS-CoV-2 seropositive individuals may be attributed to cross reaction and/or boosting of humoral response.